Den grundtvigske arv på Færøerne - Rasmussen, Peter Martin (Grundtvig-studier, 1989)
The Heritage from Grundtvig on the Faroe Islands By Peter M. Rasmussen. In the Middle Ages Faroese is a cultural language on a level with the other Nordic languages, but is pushed back in favour of Danish from around 1400. In 1899 a national movement arose, whose primary purpose was to restore the position of the mother tongue as a cultural language.In 1845 N.F.S. Grundtvig wrote a poem about the fate of the Faroese language being suppressed by Danish, and in the Danish Parliament he spoke about Faroese independence. It was Grundtvig and his son Sven who were the first to voice the idea that Faroese was to regain its position as school and church language.N.F.S. Grundtvig became of importance to the national movement through the creator of the Faroese written language, V.U. Hammershaimb, and through his son, Sven Grundtvig, and furthermore through Grundtvigian high schools in Denmark and the Faroe Islands.